Tapestry of her life - Lam, Ai Wei (2010)
Family portrait. To summarise my series in short, this photographic essay interrogates the relationship between photography, memory and documentary. It is a progress that observes the past through the present and the present through the past leading to the ultimate merger of the past and present.